The nature of privilege: intergenerational wealth in animal societies. (19th February 2022) - Smith, Jennifer E; Natterson-Horowitz, B; Alfaro, Michael E
Abstract: Wealth inequality is widespread across human societies, from pastoral and small-scale agricultural groups to large modern social structures. The intergenerational transfer of wealth privileges some individuals over others through the transmission of resources external to an individual organism. Privileged access to household wealth (e.g., land, shelter, silver) positively influences the destinies of some (and their descendants) over others in human societies. Strikingly parallel phenomena exist in animal societies. Inheritance of nongenetic commodities (e.g., a nest, territory, tool) external to an individual also contributes greatly to direct fitness in animals. Here, we illustrate the evolutionary diversity of privilege and its disparity-generating effects on the evolutionary trajectories of lineages across the Tree of Life. We propose that integration of approaches used to study these patterns in humans may offer new insights into a core principle from behavioral ecology—differential access to inherited resources—and help to establish a broad, comparative framework for studying inequality in animals. Abstract : Intergenerational transfer of wealth (e.g., tools, land, shelter) is widespread across human societies but is also ubiquitous in animals. Whereas wealth inequality has been studied extensively for humans, its study across animal species has been largely overlooked. We propose that approaches used to study wealth cross-culturally within humans, when integrated with comparative phylogenetic approaches, may yield powerful new insights into how resources are distributed within and among family groups—and across time—in animal societies.